Conditions assessment on teaching and learning facilities in UiTM Perak (Seri Iskandar Campus) / Nur Athira Kamaruddin and Hasnan Hashim - Kamaruddin, Nur Athira; Hashim, Hasnan (2023)
This research comprehensively assesses the teaching and learning facilities at Universiti Teknologi MARA Perak (Seri Iskandar Campus) in Malaysia with the objective of evaluating their condition according to the Building Condition Assessment Rating System (BCARS). The study investigates their current condition and identifies common issues, aiming to enhance the overall learning experience. The research objective is achieved by utilizing the Building Condition Assessment Rating System (BCARS) as a robust framework, employing meticulous methods such as rigorous observation (checklist) and extensive literature review for data collection. The findings, crucial in ensuring optimal facilities for students and lecturers, guide decisions on maintenance, renovation, and future planning. Key findings highlight variations in facility conditions and areas requiring attention. The study emphasizes proactive facility management and comprehensive planning for an optimal learning environment. Continuous monitoring, periodic assessments, and strategic investments in maintenance and upgrades are essential. In conclusion, this research objective offers valuable insights into the condition and issues of teaching and learning facilities, providing evidence-based guidance for facility improvement, and ensuring a high-quality learning experience.